Amicus Curiae Sebagai Bentuk Peran Serta Lembaga Swadaya Masyarakat Dalam Penegakan Hukum Pidana Lingkungan Hidup - Nabila, Ilma Aulia; Rusmiati, Elis; Imamulhadi, Imamulhadi (Widya Yuridika, 2021)
Environmental problems are collective problems that require the participation of all components of the nation, one of which includes environmental NGOs which have the right to participate in the protection and management of the environment, especially in the context of enforcing environmental criminal law. In practice, NGO participation can be a third party with an interest in pretrial, a witness or an expert in a trial or filing amicus curiae in environmental criminal cases. However, the role of environmental NGOs themselves is still a matter of debate by law enforcers because there is no place in the legislation which results in legal uncertainty for environmental NGOs to participate in environmental criminal law enforcement. This research is normative juridical. By using a descriptive analytical approach, this study aims to determine the extent of the role of environmental NGOs and the obstacles to manifesting the role of NGOs in the enforcement of environmental criminal law.